2015
DOI: 10.18805/lr.v0iof.6852
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seed pelleting on seed quality improvement in redgram (Cajanus cajan L.)

Abstract: Redgram is a protein rich staple food and contains about 22 per cent protein, which is almost three times that of cereals. Pelleting is a presowing physical seed management technique, in which growth promotive substances with protective, nutritive and invigourative function are applied on the seed to enhance the seed-soil relationship. To evaluate the efficacy of herbal powders for seed pelleting, studies were initiated with redgram cv. CO 7 with Carboxy methyl cellulose adhesive @ 200 ml per kilogram of seed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…Physiologically active substances may have activated the embryo and other associated structures which results in absorption of more water due to cell wall elasticity and development of stronger and efficient root system which leads to the increase of higher vigour index (Basra et al, 2005). Similar observation was made by Anbarasan et al (2016) in red gram.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Physiologically active substances may have activated the embryo and other associated structures which results in absorption of more water due to cell wall elasticity and development of stronger and efficient root system which leads to the increase of higher vigour index (Basra et al, 2005). Similar observation was made by Anbarasan et al (2016) in red gram.…”
Section: Resultssupporting
confidence: 88%
“…Similar results of increased gas exchange parameters was already reported by Prakash et al (2013) andSathiya Narayanan et al (2016). Increased chlorophyll index and improved photosynthetic efficiency of the plant was reported in Ocimum sanctum (Anbarasan et al, 2016).…”
Section: Resultsmentioning
confidence: 95%
“…In the present study, the added growth promoting substances in TNAU pelleting mixture facilitates nutrition, invigoration and protection to the seeds so as to enhance the better germination and seedling vigour where the seeds primed with MnSO 4 @ 0.5% and pelleted with 7 layers of TNAU pelleting mixture along with imidacloprid 70 W S @ 7 g/kg. Similar results were also observed in earlier studies (Anbarasan et al, 2016;Singh et al, 2018). Also, seed pelleting provides effectiveness in stimulating growth substances and avoids wastage of materials on broadcasting or soil application (Scott, 1989).…”
Section: Resultssupporting
confidence: 85%
“…On the other hand, different substances, including chemicals, pesticides, fertilizers, and phytohormones are mixed with seeds in the process of seed coating to increase the seed performance. Therefore, the seed-pelletized coatings can effectively increase the seed performances and can prevent them from different environmental stresses, including pest attacks (Nadia et al, 2016;Anbarasan et al, 2016). Several studies have reported the in uence of seed treatments in enhancing plant resistance against pathogens and pests.…”
Section: Introductionmentioning
confidence: 99%